2018
DOI: 10.1002/acn3.584
|View full text |Cite
|
Sign up to set email alerts
|

CSF nonphosphorylated Tau as a biomarker for the discrimination of AD from CJD

Abstract: Creutzfeldt–Jakob disease and Alzheimer's disease are characterized by the presence of elevated total‐Tau cerebrospinal fluid concentrations while the presence of hyperphosphorylated Tau forms in the cerebrospinal fluid is rather a hallmark of Alzheimer's disease. Here we aimed to investigate potential contribution of nonphospho‐Tau epitopes (non‐P‐Tau) in the discrimination between both diseases. Non‐P‐Tau cerebrospinal fluid concentration was highly increased in Creutzfeldt–Jakob disease (n = 57, 3683 ± 3599… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…In the case of phosphorylation, it is less clear if it is necessary for inducing propagation. Most studies reported that extracellular tau presents low levels of phosphorylation, an observation recently confirmed in human CSF (Le et al, 2012; Mohamed et al, 2014; Lewczuk et al, 2017; Rodriguez et al, 2017; Wang et al, 2017; Ermann et al, 2018). Aggregates composed of non-phosphorylated recombinant tau were shown to induce tau propagation (Wu et al, 2012; Mirbaha et al, 2015).…”
Section: How the Elucidation Of Tau Secretory Pathways And The Characmentioning
confidence: 78%
See 1 more Smart Citation
“…In the case of phosphorylation, it is less clear if it is necessary for inducing propagation. Most studies reported that extracellular tau presents low levels of phosphorylation, an observation recently confirmed in human CSF (Le et al, 2012; Mohamed et al, 2014; Lewczuk et al, 2017; Rodriguez et al, 2017; Wang et al, 2017; Ermann et al, 2018). Aggregates composed of non-phosphorylated recombinant tau were shown to induce tau propagation (Wu et al, 2012; Mirbaha et al, 2015).…”
Section: How the Elucidation Of Tau Secretory Pathways And The Characmentioning
confidence: 78%
“…However, in culture medium, most studies reported that tau presents either no phosphorylation or low phosphorylation levels (Mohamed et al, 2014; Rodriguez et al, 2017; Wang et al, 2017). More recently, two studies reported that an important amount of tau in the CSF of AD patients is not phosphorylated (Lewczuk et al, 2017; Ermann et al, 2018). In the case of tau aggregation, most studies did not report the presence of aggregated tau in culture medium and CSF.…”
Section: Extracellular Tau Forms: Secreted Tau Vs Csf-taumentioning
confidence: 99%
“…CSF is in direct contact with the brain parenchyma and can indirectly reflect certain pathological indications of the central nervous system (10). Changes in the abundance of many proteins (14-3-3 protein, tau et al) in CSF can be used in the diagnosis of CJD (1114). RT-QuIC has proved to be a very valuable diagnostic CSF test for sCJD (7).…”
Section: Introductionmentioning
confidence: 99%
“…Another tau related biomarker, non-phospho-Tau (non-P-Tau), was found to be significantly elevated in CJD (3683 ± 3599 pg/mL) compared to AD (148 ± 219 pg/mL) and neurological controls (62 ± 40 pg/mL). Non-P-Tau also significantly improved differentiation of CJD from AD (99%) compared to total-Tau (90%), P-Tau (62%) and 14-3-3 (91%) [ 44 ].…”
Section: Markers For Rapid Neurodegenerationmentioning
confidence: 99%